Fiber sources in diets for newly weaned piglets - Pascoal, Leonardo Augusto Fonseca [UNESP]; Thomaz, Maria Cristina [UNESP]; Watanabe, Pedro Henrique [UNESP]; Ruiz, Urbano dos Santos [UNESP]; Ezequiel, Jane Maria Bertocco [UNESP]; Amorim, Alessandro Borges [UNESP]; Daniel, Everton [UNESP]; Masson, Guido Carlos Iselda [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
This experiment was carried out to evaluate the effects of purified cellulose, soybean hulls and citrus pulp in the diet of weaned piglets. A total of 72 piglets (36 castrated males and 36 females) weaned at 21 days of age (BW 6.45±0.66 kg) was distributed according to a randomized block design, for evaluation of performance, transit time, diarrhea incidence and blood parameters of piglets which received diets containing different sources of fiber. The experimental diets were: control diet - diet composed of corn, soybean meal and a source of lactose; control + 1.5% purified cellulose; control + 3% soybean hull and control + 9% citrus pulp. The inclusion of purified cellulose, soybean hulls and citrus pulp in diets of weaned piglets did not affect the performance or transit time of diets in the gastrointestinal tract. However, the use of purified cellulose reduced incidence of diarrhea. The use of purified cellulose, soybean hull and citrus pulp in the diet of weaned piglets does not affect performance or gastrointestinal transit time. The addition of purified cellulose promotes a beneficial effect to control the diarrhea in weaned piglets.
Keywords: Dietary fiber; gut microbiota; Intestinal health; Weaning